Akulturasi Stress Siswa Mutasi dari Sekolah di Luar Negeri - Maulidha Sholehah; Susi Fitri; Lara Fridani (Indonesian Journal of Educational Counseling, 2020)
ACCULTURATION OF MUTATIONAL STRESS STUDENTS FROM SCHOOLS OF FOREIGN COUNTRY. The aims of this study was to obtain the results of the research acculturation emphasizes student transfer from overseas schools in the international class XI program of Bosowa Al Azhar Cilegon, Banten High School. The researcher used two research methods namely qualitative method with indept interview, observation and using a questionnaire from the Acculturative Stress Scale for International Students (ASSIS) and open questions as data reinforcement, all students reported stress acculturation. Interestingly, however, responding to open questions asks students to consider themselves to increase pressure related to opposition, feelings of feelings, and academic problems. The question that was asked between interviews, observation, ASSIS and open questions discussed the questions of international class XI students at Bosowa Al Azhar Cilegon, Banten secondary school and drew attention when developing complementary planning for the purposes of the study. The results of this study are that this study is single data, both of these international class students, respectively, use Quartil in calculating the statistics. Quartil is the calculation of statistical data for research in which the data is single, not in groups. The whole correct answer for ASSIS 36-item is 180. Journal of ASY score results is 128 and MKB is 112. Accessible by ASY depends on high category and MKB depends on high category.